Chiral quaternary ammonium ionic liquids derived from natural dehydroabietylamine and their potential application in chiral molecular recognition. (9th January 2023) - Yan, JingJing; Zhu, Yi; Hu, Gang; Liang, Qinghui; Ge, Li; Yang, Kedi
Abstract: A series of chiral ionic liquids (CILs) based on a quaternary ammonium core substituted with (+)-dehydroabietylamine (DAA) moiety have been synthesized, which are used for the chiral discrimination of non-ionic racemic carboxylic acid and derivatives. The enantioselective recognition ability of the obtained DAA-CILs was investigated using ( rac )-mandelic acid and its derivatives as substrates. The results showed that the choice of the anion was crucial for the chiral discrimination of these DAA-CILs. In general, bistrifluoromethanesulfonimide anion (NTf2 - ) resulted in the improvement and a broad spectrum of enantioselectivity of the CILs. The alkyl chain attached to the DAA group and quaternary ammonium cation was also responsible for the chiral discrimination, and the C3 or C4 carbon chain was favorable for the chiral molecule recognition ability of the CILs. A molecular simulation of the diastereomeric interactions between the selected [DAAPrTMA]NTf2 CIL and racemic α -methoxy mandelic acid ( α -MPAA) achieved a well understanding of the chiral recognition mechanism. Additionally, the optical purity of α -MPAA could be detected via NMR analysis easily and quickly. This work leads us to develop new CILs with good molecular recognition ability, DAA-based quaternary ammonium salts. Graphical abstract: Image 1 Highlights: A series CILs based on a quaternary ammonium core substituted with (+)-dehydroabietylamine moiety were synthesized. The DAA-CILs showed enantioselective recognition ability to ( rac )-mandelic acid and its derivatives. The anion and alkyl chain of DAA-CILs was crucial for their chiral discrimination. DFT was employed to analyze the non-covalent interactions of the chiral recognition mechanism.